Long-Term Impact of COVID-19 on Global Air Transport: Analyzing Recovery Patterns and Strategic Responses - H. Abdelati, Mohamed (Frontiers in Sustainable Science and Technology, 2025)
The outbreak of COVID-19 has tremendously affected the world’s aviation business by causing significant losses and organizational difficulties. Specifically, in this paper, the analysis of the changes in the conditions of the pandemic’s effect on the financial and traffic indicators of the companies in the aviation field and patterns of their operational strategies is considered. Based on the data, which covers January 2019- December 2021, it is established that there are revenue and passenger indicators that decrease with only partial restoration by the end of 2021. Various financial records obtained from the airline reports reveal massive reductions in revenue and increased expenses on cancellations and the grounding of aircraft. Using the passenger traffic data from IATA and ACI, it is possible to study the passenger volumes and analyze the time series to determine main recovery tendencies. Primary data from the surveys conducted in 2020 and 2021 to understand the passengers’ confidence and travel inclination revealed a gradual recovery. This paper also focuses on other adaptive actions by airlines, like route changes and operation strategies to minimize losses. The results imply a focus on effective crisis management and policy measures to promote the improvement of resilience in businesses and industries. The issues and guidelines for future preparation are the creation of financial buffers, the implementation of contingent organizational structures, and the development of additional funding sources. Based on the current study, the following recommendations are proposed to policymakers, airline operators, and other related stakeholders.